The radioactive 3D-printed template-assisted CT-guided 125I seed implantation for refractory bone metastases: A multicenter retrospective analysis of efficacy, safety, and immune function changes - Guang Sheng Zhao; Hou Ze Zhou; Qiu Shi Wang; Xin Yu Zhou; Jin Bo Sun; Fei Gao; Ruo Yu Wang; Zhe Wang; Jun Zhou; Song Liu; Bu Qiang Zhuang (PLoS ONE, 2026)
Objective To comprehensively evaluate the efficacy and safety of three-dimensional (3D)-printed template-assisted CT-guided 125 I seed implantation for refractory bone metastases in a multicenter cohort, to explore its impact on systemic immune function and to identify potential mechanisms. Methods This retrospective analysis was conducted on 253 patients with refractory bone metastases who were continuously admitted to Affiliated Zhongshan Hospital of Dalian University, Linyi Cancer Hospital, The Affiliated Hospital of Xuzhou Medical University, Dalian Public Health Clinical Center, and The Second Hospital of Dalian Medical University. The onset time and the duration of pain relief were recorded. The therapeutic efficacy was evaluated by comparing pre- and postoperative Daily Oral Morphine Equivalent Consumption (OMEC), Numerical Rating Scale (NRS) for pain, Quality of Life (QOL) scores, and Karnofsky Performance Status (KPS) scores, as well as by measuring the quantitative changes in target lesion volume and Hounsfield unit (HU) values on imaging before and after the procedure. According to Response Evaluation Criteria in Solid Tumors version 1.1, the objective response rate (ORR) and disease control rate (DCR) were calculated to evaluate tumor response. Flow cytometry was used to detect and compare pre- and postoperative proportions of CD3 + CD16 + /CD56 + natural killer-like T (NKT) cells and CD3 − CD16 + /CD56 + NK cells, interleukin (IL)-17A level, and CD4 + /CD8 + T-cell ratio, to assess the changes in host immune function after treatment. Local progression-free survival (LPFS) and overall survival (OS) were calculated, and adverse events were documented. Results All patients completed 3D-printed template-assisted CT-guided 125 I seed implantation, with a procedural success rate of 100%. The clinical symptoms improved after treatment; the median onset time to pain relief was 3.5 days, and the median duration of relief was 10.7 months. The OMEC values and the NRS scores were significantly lower than those before procedure ( P < 0.05), whereas QOL and KPS scores were significantly higher ( P < 0.05). The radiologic evaluation showed that ORR and DCR were 42.29% and 69.56%, and 79.05% and 88.93%, respectively, at 1 and 6 months after implantation. The target lesion volumes reduced significantly ( P < 0.05), whereas the HU value increased significantly ( P < 0.05), indicating tumor necrosis and osteoblastic repair. The median LPFS was 14.1 months, and the median OS was 19.5 months. The immune function analysis revealed enhanced antitumor immune response, reflected by significant increases in the proportions of NKT cells, NK cells, and CD8 + T cells, a decrease in IL-17A level, and a trend toward normalization of the CD4 + /CD8 + ratio ( P < 0.05). Adverse events mainly consisted of transient local pain of Common Terminology Criteria for Adverse Events grades 1–2. No uncontrollable major bleeding, needle-track seeding, or other severe complication, and no treatment-related death occurred. Conclusions The 3D-printed template-assisted CT-guided 125 I seed implantation was a safe and effective treatment for refractory bone metastases. It provided durable local tumor control and pain relief, and was accompanied by systemic immunological changes. These changes correlated with clinical improvements, suggesting a potential immunological component to the therapeutic effect. This therapy therefore provided a promising treatment strategy for refractory bone metastases.